Diachasmimorpha longicaudata Parasitism Response to Medfly Host Fruit and Fruit Infestation Age - Harbi, Ahlem; De-Pedro, Luis; Ferrara, Fernando; Tormos, José; Chermiti, Brahim; Beitia, Francisco J.; Sabater-Munoz, Beatriz (2020)
The parasitoid Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae) is increasingly being used in integrated pest management (IPM) programs as a biological control agent in order to suppress tephritid fruit flies of economic importance. Innate and acquired behavioral responses-such as pest host fruit preference-of parasitoids can modulate their efficiency in the field and should be taken into consideration prior to parasitoid species' selection for mass-rearing. We have assessed the influence of medfly-infested (two infestation ages, 1 and 4-d-old) and uninfested fruit species on host preference and efficiency of D. longicaudata by using a multistep assay including olfactory, laboratory and semi-field trials. We found that D. longicaudata was significantly more attracted to medfly-infested apples for both infestation ages, with the oldest being the most preferred. D. longicaudata exhibited a significant preference among the four fruits tested. The implications of these behavioral responses of D. longicaudata to medfly host fruits and infestation age are discussed in relationship to its use in IPM programs in the Mediterranean basin area.